Implementation of the Forum Lapor Feature in the Manado Post Application to Enhance User Interaction - Lengkong, Oktoverano; Salainti, Juan Michael (12th International Scholars Conference 2025, 2026)
The Manado Post application is a digital platform that delivers real-time news to the people of North Sulawesi. Despite its broad user base, the level of user interaction within the application remains low. To address this issue, this study implements a "Forum Lapor" feature to enhance user engagement. This feature enables users to report local incidents directly through the app, facilitating active participation. The development of the feature utilized the Scrum methodology, promoting iterative progress and flexibility, while Firebase Realtime Database was employed to manage real-time data storage and synchronization. After implementation, the conversion rate of passive to active users increased significantly, especially among users who previously only consumed news content. The introduction of this participatory feature has proven effective in boosting user interaction and expanding the application’s role as an interactive communication platform. The study highlights the importance of integrating user-generated content to foster community engagement and improve application retention rates.